Особливості анатомічної будови листкової пластинки представників роду Pittosporum Banks et Soland. ex Gaertn. в умовах промислового інтер’єру - Boyko, L.І. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The anatomic features of leaf plate at 7 species of Pittosporum Banks et Soland. ex Gaertn genus are studied. The changes of anatomic indexes and pigmentary system in an assimilatory vehicle at different conditions of growing are defined.